Effects of irrigation and nitrogen management on phyllosphere microbial communities of silage maize - Liuxing Xu; Changjing Chen; Chenggang He; Ahmed M. Abd El Tawab; Qinhua Liu; Hua Jiang (PeerJ, 2025)
Silage maize (Zea mays) is a significant source of animal roughage in many countries. Few studies have revealed the specific impacts of agronomic measures on harmful or beneficial microbial species (based on plant health or utilization) in silage maize. The aim of the present study was to investigate the effects of three maturity stages (big trumpet, milk, and dough) × two irrigation amounts (1,200 m3 hm−2 (IA1,200) and 2,400 m3 hm−2 (IA2,400)) × three nitrogen (N) application rates (160 kg hm−2 (low), 240 kg hm−2 (medium), and 320 kg hm−2 (high)) on the bacterial community structure of the silage maize phyllosphere. Irrigation amounts and N application rates did not affect silage maize leaves’ chemical or physiological properties, but influenced the bacterial community structure of silage maize phyllosphere. There were higher relative abundances of beneficial (Pseudomonas, Rhodococcus, Achromobacter, and Myroides) or harmful (Bordetella and Ralstonia) microbial in IA2,400 compared with IA1,200. Plant pathogenic bacteria (Erwinia and Serratia) were found to have the highest relative abundance at the low N application rates. In meta-analysis, some bacteria impacted the phytosanitation and nutrition quality of forage, encompassing Ralstonia, Pantoea, Dokdonella, Vogesella, Erwinia, Serratia, Pseudomonas, and Bordetella. Based on the yield, plant health, and potential fermentation quality of silage maize, we recommend using an irrigation amount of 2,400 m3 hm−2 and an N application rates of 240 kg hm−2 for agricultural production and harvesting silage maize at the milk stage.